Screening and Optimization Consortium Technique of the Bacillus megatherium and Saccharomyces cerevisiae Microbial Consortium for Ethanol Detection - Nurdiani Nurdiani; Dyah Iswantini; Novik Nurhidayat; Wulan Tri Wahyuni; Agus Kartono (Syarif Hidayatullah State Islamic University, 2023)
Determination of alcohol content is very important in the food and beverage industry. Biosensor is an alternative to measuring ethanol content. Alcohol biosensors with a single microbe still have a narrow measurement area at ethanol concentrations, so a microbial consortium is needed to widen the range of measured ethanol concentrations. Therefore, it is necessary to screen the microbes from Bacillus sp and S. cerevisiae which have the potential to produce alcohol dehydrogenase (ADH) enzymes and optimize the consortium technique that can provide the best response to oxidation currents. In the yeast microbial screening of 14 S. cerevisiae isolates and 5 Bacillus sp isolates, it can be concluded that for the 14 yeast S. cerevisiae isolates that have the potential to produce ADH enzymes, there is one isolate with the SCRF code. For the 5 bacterial isolates of Bacillus sp that have the potential to produce ADH enzymes, all Bacillus isolates with the code Bacillus megatherium 29/9/14, Bacillus megatherium 23/6/22, Bacillus 6, Bacillus 53, and Bacillus 55. Based on the oxidation current data, Bacillus megatherium 23 /6/22 produces the highest current compared to other Bacillus isolates. The consortium technique that provides the highest current is the method of mixing 1:1 (µL) microbial suspension in an Eppendorf container. Optimization of the consortium's biofilms using the Response Surface Method was produced at 10 days of age, pH 7.5, and 75 µL of microbial suspension dripping volume.